The Diagnostic Value of D-dimer, Procalcitonin and CRP in Acute Appendicitis - Kaya, Bulent; Sana, Baris; Eris, Cengiz; Karabulut, Koray; Bat, Orhan; Kutanis, Riza (Ivyspring Int Publ, 2012)
BACKGROUND: The early diagnosis of acute abdomen is of great importance. To date, several inflammatory markers have been used for the diagnosis of acute abdominal conditions, including acute appendicitis. The aim of this study was to evaluate the diagnostic utility of D-dimer, Procalcitonin (PCT) and C-reactive protein (CRP) measurements in the acute appendicitis. METHODS: This prospective study was conducted between March 1st, 2010 and July 1st, 2011. In this period, seventy-eight patients were operated with the diagnosis of acute appendicitis, and D-dimer, PCT and CRP levels of the patients were measured. The patients were grouped as phlegmonous appendicitis (Group 1), gangrenous appendicitis (Group 2), perforated appendicitis (Group 3) and negative appendectomy (Group 4) according to the surgical findings and histopathological results. RESULTS: Of 78 patients, 54 (69.2%) were male and 24 (30.8%) were female, and the mean age was 25.4 +/- 11.1 years (range, 18 to 69 years). 66 (84.6%) patients had increased leukocyte count (white blood cell count). The PCT values were higher than the upper normal limit in 20 (25.6%) patients, followed by D-dimer in 22 (28.2%) patients and CRP in 54 (69.2%) patients. The diagnostic value of leukocyte count and CRP in acute appendicitis was higher than that of the other markers, whereas leukocyte count showed very low specificity. CRP values were higher in perforated appendicitis when compared with the phlegmonous appendicitis (p<0.05). However, PCT and D-dimer showed lower diagnostic values (26% and 31%, respectively). CONCLUSION: An increase in CRP levels alone is not sufficient to make the diagnosis of acute appendicitis. However, CRP levels may differentiate between phlegmonous appendicitis and perforated appendicitis. Due to their low sensitivity and diagnostic value, PCT and D-dimer are not better markers than CRP for the diagnosis of acute appendicitis.
Keywords: Appendicitis; D-dimer; Procalcitonin; C-reactive protein